Calcium dynamics in microbialite‐forming exopolymer‐rich mats on the atoll of Kiritimati, Republic of Kiribati, Central Pacific. Issue 2 (17th December 2014) - Ionescu, D.; Spitzer, S.; Reimer, A.; Schneider, D.; Daniel, R.; Reitner, J.; de Beer, D.; Arp, G.
Abstract Microbialite‐forming microbial mats in a hypersaline lake on the atoll of Kiritimati were investigated with respect to microgradients, bulk water chemistry, and microbial community composition. O2, H2S, and pH microgradients show patterns as commonly observed for phototrophic mats with cyanobacteria‐dominated primary production in upper layers, an intermediate purple layer with sulfide oxidation, and anaerobic bottom layers with sulfate reduction. Ca2+ profiles, however, measured in daylight showed an increase of Ca2+ with depth in the oxic zone, followed by a sharp decline and low concentrations in anaerobic mat layers. In contrast, dark measurements show a constant Ca2+ concentration throughout the entire measured depth. This is explained by an oxygen‐dependent heterotrophic decomposition of Ca2+‐binding exopolymers. Strikingly, the daylight maximum in Ca2+ and subsequent drop coincides with a major zone of aragonite and gypsum precipitation at the transition from the cyanobacterial layer to the purple sulfur bacterial layer. Therefore, we suggest that Ca2+ binding exopolymers function as Ca2+ shuttle by their passive downward transport through compression, triggering aragonite precipitation in the mats upon their aerobic microbial decomposition and secondary Ca2+ release. This precipitation is mediated by phototrophic sulfide oxidizers whose action additionally leads to the precipitation of part of the available Ca2+ as gypsum.